Implications on Livelihoods and the Environment of Uptake of Gasifier Cook Stoves among Kenya’s Rural Households - James K. Gitau; Jane Mutune; Cecilia Sundberg; Ruth Mendum; Mary Njenga (Applied Sciences, 2019)
A majority of people in developing countries use biomass energy for cooking and heating due to its affordability, accessibility and convenience. However, unsustainable biomass use leads to forest degradation and climate change. Therefore, this study was carried out in Kwale County, Kenya, on the use of a biochar-producing gasifier cook stove and implications of its uptake on livelihoods and the environment. Fifty households were trained and issued with a gasifier for free. After 2–3 months of gasifier use, a survey was conducted to investigate the implications of its uptake. The direct impacts included reduced fuel consumption by 38%, reduced time spent in firewood collection, reduced expenditure on cooking fuel, diversification of cooking fuels, improved kitchen conditions and reduced time spent on cooking. The potential benefits included income generation, increased food production, reduced impacts on environment and climate change and reduced health problems. Improved biomass cook stoves can alleviate problems with current cooking methods, which include inefficient fuel use, health issues caused by smoke, and environmental problems. These benefits could contribute to development through alleviating poverty and hunger, promoting gender equality, enhancing good health and sustainable ecosystems and mitigating climate change. The study recommends the promotion of cleaner cooking stoves, particularly gasifiers, among households in rural areas while paying attention to user needs and preferences.